Preparation of Pt/ATO catalysts for electrocatalysis in direct alcohol fuel cell - Li Fang (2018)
© 2016, Chiang Mai University. All rights reserved. Pt loaded on Antimony doped Tin dioxide (Pt/ATO) catalyst was successfully prepared by using ultrasonic dispersion and ethanol reduction and characterized by XRD combined with cyclic voltrammetry (CV). The comparison of catalytic performance of Pt/ATO with the catalysts Pt/C, Pt/SnO2and Pt/(C+SnO2) for methanol and ethanol electrooxidation was studied by means of CV and chronoamperometry (CA). Comparing to the other catalysts, the catalytic activity and stability of Pt/ATO were improved significantly by doping Sb into the SnO2crystal lattices. Moreover, the remarkable enhancement of the selectivity of Pt/ATO for CO2production was also observed in the electrocatalytic oxidation of the ethanol.